A review of the potential of seawater brine for enhancing food security in hot arid climates: A case study of Qatar - Nadira Salsabila (16855101) (2025)
This study explores Qatar's utilisation of seawater to support food security, emphasising the innovative strategies and technological advancements to address the environmental and agricultural challenges posed by rejected brine from desalination processes. It examines various brine treatment and disposal methodologies, highlighting the environmental impacts and proposing sustainable solutions to mitigate these effects. The discussion further explores the potential of electrodialysis and other emerging technologies for converting rejected brine into valuable agricultural resources, thereby contributing to food security in arid regions. Through a comprehensive review of current research and potential innovations, this study highlights the critical intersection of water resource management, environmental sustainability, and food production, particularly in Qatar's unique geographical and climatic conditions. Other Information Published in: Journal of Environmental Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jenvman.2025.124216